2003
DOI: 10.1097/01.pec.0000086240.54586.04
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Pneumonia Complicated by a Hyponatremic Seizure

Abstract: We present the case of a 6-week-old male infant who had a convulsion due to pertussis pneumonia. He was admitted to our emergency department because of lethargy and hypothermia. He developed a generalized tonic-clonic convulsion, requiring various treatments, including artificial ventilation. A chest CT showed bilateral pneumonia and laboratory data revealed hyponatremia with other features of the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Although SIADH has been recognized as a cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…No earlier data are available on the etiology of pediatric pneumonia and the risk of electrolyte disturbances. In a case report, pertussis was associated with severe HN and seizures in a 6-week-old infant [34]. Studies of adults have suggested that patients with CAP caused by Legionella pneumophila are at a higher risk of developing HN than are those suffering from CAP due to other germs [35][36][37], such as Streptococcus pneumoniae, Mycoplasma pneumoniae or Chlamydia pneumoniae, more commonly seen in pneumonia in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…No earlier data are available on the etiology of pediatric pneumonia and the risk of electrolyte disturbances. In a case report, pertussis was associated with severe HN and seizures in a 6-week-old infant [34]. Studies of adults have suggested that patients with CAP caused by Legionella pneumophila are at a higher risk of developing HN than are those suffering from CAP due to other germs [35][36][37], such as Streptococcus pneumoniae, Mycoplasma pneumoniae or Chlamydia pneumoniae, more commonly seen in pneumonia in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Japonya'dan yayınlanan bir çalışmada ise Hiponatremi ile ASYE etkenleri arasında herhangi bir ilişki bulunamamıştır (7). Ancak boğmaca sonrası pnömoni gelişen 6 haftalık bir erkek hastada ağır hiponatremi nedeniyle konvülziyon görüldüğü bildirilmiştir (14). Erişkinlerde ise legionella pneumophila'ya bağlı gelişen pnömonilerde hiponatreminin daha sık görüldüğü saptanmıştır (15).…”
Section: Discussionunclassified